Prescribing Pattern of NSAIDs in Orthopedic Department of Dhaka Medical College Hospital - Rahman, Kazi Afzalur; Kamal, AHM Mostafa; Akhter, Sanjida; Khatun, Khadeza; Afroz, Rumana; Akther, Tahmina (Journal of Dhaka Medical College, 2017)
Context : Drug therapy is the most commonly used method in disease treatment in general practice. The pattern of drug prescription are often inappropriate and need for registration of these patterns is essentian in an effort to improve prescribing standard. Nonsteroidal antiinflammatory drugs (NSAIDs) are a drug class that groups together drugs that provide analgesic (pain-killing) and antipyretic (fever-reliefing) effects, and, in higher doses, anti-inflammatory effects. Non steroidal anti inflammatory drugs are the most common drugs prescribed in the world over specially in the orthopedic department. The study of prescribing pattern of NSAIDs in the orthopedic department was conducted to monitor, evaluate and if necessary suggest modification in the prescribing behavior of the medical practitioner to make it rational and cost effective. Material and Methods: The present study was performed on 300 (Three hundred) prescriptions from both admitted and outpatients (OPD) of the orthopedic department of Dhaka Medical College Hospital, Dhaka. The check list type of data was collected with prior permission from the concern department and the authority. The study was cross sectional analytical type and was conducted in the department of Pharmacology, Dhaka Medical College, Dhaka, from July 2010 to June 2011. Result : In case of OPD patients most common NSAIDs prescribed to the patients were aceclofenac (44.7%); followed by diclofenac (23.3%). Other NSAIDs were naproxen, ketorolac and ibuprofen 8%, 15.3% and 5.4% respectively. In case of admitted patients most common NSAIDs prescribed to the patients were ketorolac (54.7%) followed by diclofenac (24.0%). Conclusion: Non steroidal anti inflammatory drugs were the main prescription drug for both indoor and outdoor patients in the orthopedic department. Aceclofenac in outdoor and ketorolac in indoor were the most common NSAIDs drug used. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 58-60